2021
DOI: 10.56093/ijas.v91i5.112983
|View full text |Cite
|
Sign up to set email alerts
|

Intergeneration correlation and parent-offspring regression in rust resistance derived F4 and F5 generations in bread wheat

Abstract: The present investigation aimed to determine the intergeneration correlation and parent-offspring regression in F4 and F5 generations of two wheat crosses, WH 1105 × WH 711 and RAJ 3765 × WH 711 grown during the rabi 2015-16 and 2016-17 in research area of Wheat and Barley Section, CCS HAU, Hisar. Correlation studies indicated that grain yield/plant showed a significant positive correlation with almost all the yield attributing traits which may be considered as prime traits during selection. Biological yield/p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…In this work, regression estimates showed that these features were less affected by the environment and that selection based on their phenotypes in these generations was heritable. The parent-progeny regression technique is used to determine the narrow-sense heritability of variables that result from additive genetic variance (Rani et al, 2021). For all the characteristics included in this analysis, the correlation coefficient was highly significant.…”
Section: Kurtosis Value Of 1 Indicates Mesokurtic Behaviourmentioning
confidence: 99%
“…In this work, regression estimates showed that these features were less affected by the environment and that selection based on their phenotypes in these generations was heritable. The parent-progeny regression technique is used to determine the narrow-sense heritability of variables that result from additive genetic variance (Rani et al, 2021). For all the characteristics included in this analysis, the correlation coefficient was highly significant.…”
Section: Kurtosis Value Of 1 Indicates Mesokurtic Behaviourmentioning
confidence: 99%